Risk for life-threatening arrhythmia in newly diagnosed peripartum cardiomyopathy with low ejection fraction: a German multi-centre analysis - Duncker, David; Thomas, Dierk (Clinical research in cardiology, 2017)
Introduction: Peripartum cardiomyopathy (PPCM) is a rare cardiomyopathy characterized by an acute reduction in left ventricular ejection fraction (LVEF). Sudden deaths during the course of PPCM are reported to be elevated, the underlying mechanisms remains unknown. The aim of the present multi-centre study was to evaluate the arrhythmia burden in a multi-centre approach in patients with PPCM using a wearable cardioverter/defibrillator (WCD).